(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
The purpose of this study was to analyze the role of education in the context of national competitive growth. What is competitive economic growth, what does education encompass, what is its role in ensuring the competitive growth of the national economic system, and what is the impact of education on competitive growth through the lens of innovative development and competitive growth? We will answer these questions in this article. The relevance and scientific novelty of this study lie in the fact that it is the first scientific study to examine the role of education in the context of ensuring competitive growth. This study enhances the practical and applied nature of this research and further updates the results. Every country sets the goal of ensuring economic growth, but not every country achieves this through the lens of sustainability, environmental friendliness, innovation, and social development. The article provides the author’s definition of competitive growth of the national economy, which is economic growth based on the sustainable development of the economic system, based on the synergy of competitiveness and innovative development factors, allowing the country to occupy an advantageous position in the global economy. Education plays a crucial role in this. Social institutions today are most often viewed as historically established, stable forms of organizing people’s joint activities, as well as the relationships that develop between them in the process of achieving socially significant goals. First among these is the institution of science, which is a kind of paired category with the institution of production. Like the latter, it is fundamental to the national economy in terms of material nature. In terms of goal-setting, its role is to produce verified scientific knowledge oriented toward the evolutionary development of society. When examining the structure of the national innovation system, science is typically positioned in the same block as education. This applies primarily to higher education, as it is there that individuals acquire basic creative competencies, making the educational process a crucial factor in increasing national competitiveness. To meet the general requirements of macroeconomic competitiveness, educational institutions must build knowledge transfer processes around modern functional innovations. The foundation of innovative progress lies in the institution of education, which ensures the development of a highly qualified workforce necessary to maintain high rates of economic growth and the state’s competitiveness. This article examines in detail the characteristics of the institution of education, highlights its specific features, and analyzes its networked form. In this article, we will examine a scientifically based approach to defining the role of educational institutions in ensuring competitive growth.